2018
DOI: 10.1021/acsnano.8b00108
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric-Nanogenerator-Based Soft Energy-Harvesting Skin Enabled by Toughly Bonded Elastomer/Hydrogel Hybrids

Abstract: A major challenge accompanying the booming next-generation soft electronics is providing correspondingly soft and sustainable power sources for driving such devices. Here, we report stretchable triboelectric nanogenerators (TENG) with dual working modes based on the soft hydrogel-elastomer hybrid as energy skins for harvesting biomechanical energies. The tough interfacial bonding between the hydrophilic hydrogel and hydrophobic elastomer, achieved by the interface modification, ensures the stable mechanical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
196
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 273 publications
(228 citation statements)
references
References 62 publications
(84 reference statements)
3
196
0
Order By: Relevance
“…Until now, only a few hydrogels have been reported that exhibit good resistance to drying or swelling . However, none of the hydrogels developed thus far have shown stability in both air and water, which limits their practical applications .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, only a few hydrogels have been reported that exhibit good resistance to drying or swelling . However, none of the hydrogels developed thus far have shown stability in both air and water, which limits their practical applications .…”
mentioning
confidence: 99%
“…Hydrogels with drying resistance were originally developed by incorporating high‐density hygroscopic salts in the bulk hydrogel system or by encapsulating the hydrogels within an elastomeric material . However, the former may produce a toxic effect owing to the presence of high‐density salts, while the latter makes hydrogels impermeable to many important chemicals, such as ions and drug molecules, eliminating an important function of hydrogels.…”
mentioning
confidence: 99%
“…Thus, from the material point of view, the electron affinity, surface function groups, as well as work function are important factors affecting the output performance of TENG. A vast number of advanced materials have been explored, including graphene, MXenes, hydrogels, aerogels, black phosphorus (BP), etc.…”
Section: Flexible Tengmentioning
confidence: 99%
“…Copyright 2016, Wiley‐VCH. D, TENG‐based E‐skins . Copyright 2017, The American Association for the Advancement of Science.…”
Section: Flexible Tengmentioning
confidence: 99%
See 1 more Smart Citation